ANALISIS YURIDIS KEWAJIBAN MODAL INTI MINIMUM BANK UMUM BERDASARKAN POJK NOMOR 12/POJK.03/2020 DALAM MENJAGA STABILITAS SISTEM PERBANKAN INDONESIA - Katleya Puspa Nagari (Jurnal Hukum Lex Generalis, 2024)
Banking stability is the foundation of the national economy, supported by the regulation of the minimum core capital of commercial banks based on POJK Number 12/POJK.03/2020. This policy requires a minimum core capital of Rp3 trillion, in line with Basel III standards to strengthen the structure, competitiveness and efficiency of the banking sector. The phased implementation and relaxation of time allowed the majority of banks to meet this requirement, despite facing challenges such as investors and consolidation. Banks that fail to meet the requirements face administrative sanctions that encourage capital improvements. This policy is proven to improve capital adequacy ratio (CAR) and efficiency, strengthen the national banking structure, and support economic stability.